Toxicity and antiplasmodial evaluation of Malaysian Plectranthus amboinicus leaves extract - Ramli, Norazsida; Oothuman, Pakeer; Bakhtiar, M. Taher; Elhady, Hassan Mohamed (2013)
This study was conducted to evaluate the toxicity and antiplasmodial properties of Malaysian Plectranthus amboinicus. Phytochemical analysis on the crude ethanolic extract of leaves of Malaysian P. amboinicus (Lour) Spreng was carried out to delineate the presence of its chemical constituents like Alkaloid, Flavonoid, Saponin, Triterpenoid, Steroid, and Phenolic components. Acute oral toxicity at one dose level of 5000 mg/kg as per OECD Guideline for Testing of Chemicals 423 was conducted to evaluate the safeness of this extract to be consumed by humans. 20 mice were divided into one control group and one experimental group. All the mice were observed for signs of toxicity, mortality, weight changes and histopathological changes. Antimalarial activity of different extract doses of 50, 200, 400 and 1000 mg/kg were tested in vivo against Plasmodium berghei (PZZ1/100) infections in mice (5 mice for each group) during early, established and residual infections. The results revealed that the extract contained only flavonoid. The acute oral toxicity test revealed that no mortality or evidence of adverse effects was seen in the treated mice. Studies on histopathological examination of kidneys and livers showed normal architecture suggesting no morphological changes. The extract significantly reduced the parasitemia by the 50 (p=0.000), 200 (p=0.000) and 400 mg/kg doses (p=0.000) in the in vivo prophylactic assay. The %chemo-suppression was calculated as 83.33% for 50mg/kg dose, 75.62% for 200 mg/kg dose and 90.74% for 400 mg/kg dose. Body weight of all treatment groups; T1, T2, T3 and T4 also showed enhancement after 7 days post-treatment. Statistically no reduction of parasitemia calculated for curative and suppressive test. Thus, the isolation of active compound of this extract may give a promising drug molecule to be used as prophylactic agent of Plasmodium berghei infection in mice